Rapidly deployable beam-switched 802.11 wireless distribution system - Pascua, John Cezar L.
Point-to-point connectivity in rural areas poses two main problems: difficulty in installation and antenna alignment on both endpoints of the connection. A balloon-deployed switched beam antenna system is proposed to address the need for a rapidly deployable wireless distribution system that costs less than existing connectivity solutions. A main switching board capable of detecting the received signal strength (RSS) of four antennas was constructed. The main switching board also contains provisions for switching between the antennas, and connecting the selected antenna to a router. A microcontroller unit was configured to monitor the RSS of all four antennas and control the main switching board to select the antenna with highest RSS. A Yagi-Uda antenna was constructed but was left untested. The system is powered through power over Ethernet (PoE) and appropriate voltage step down converters.